Desain Kamus Semantik Pola Kalimat dalam Al-Qur'an: Taṣmīm al-Qāmūs al-Dalāly fī Nimṭ Kalimāt Al-Qur’ān - Mitrajati, Kenyo; Baroroh, R Umi (Study Program of Arabic Language Teaching, 2023)
This study aims to formulate the design of a semantic dictionary of Arabic sentence patterns in the Qur'an. The research also aims to complement research on existing Al-Qur'an Arabic dictionary designs, especially for Al-Qur'an Arabic lessons in Indonesia. This research is qualitative with a literature study approach. Where the research data were obtained from the primary reading sources of the Al-Qur'an and the book Mu'jam al-Furūq al-Dalāliyyah fī al-Qur'ān al-Karīm and then developed into dictionary designs. The results of the study show that the design of this semantic dictionary can be considered a book dictionary design that supports the understanding of a book through the presentation of the meaning of the vocabulary, syntax, and morphology recorded in the book. The design of the semantic dictionary of sentence patterns in the Qur'an that the researcher offers is by writing the column rows, numbers, names of surahs and verses, the sentence patterns that appear, and the text of the verses.